MENAPAKI KEMBALI SEJARAH DAN GERAKAN ISU ROMUSHA DI INDONESIA - Anugrah Saputra (Jurnal Renaissance, 2018)
The research discuss about forced labor practices in Indonesia under Japanese Military invation. The focus of this paper is to highlight how the idea of forced labor context, the mobilization process and to describing, also reveals preliminary findings on the ground in relation to Romusha's case study at village in Boyolali. In this papaer also will be presented how the future of that issues and humanitarian movement Romusha in Indonesia recently. I used literature and field studies by presenting some of the survivor (ex-romusha). The result of this study bring the conclusions of discussion and history alignment to the younger generation should be continue  and so that we can moving into a better future.Keywords: romusha in indonesia; japanese military invation